2015
DOI: 10.15171/rdme.2015.013
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Organizational Citizenship Behavior and Educational Performance of Faculty Members in Tabriz University of Medical Sciences- 2014

Abstract: Introduction:Regarding the educational goals of university and academic performance, it seems that organizational citizenship behavior (OCB) is one of the effective variables in increasing the educational performance of university faculty members. The present study aims to investigate the relationship between organizational citizenship behavior (OCB) and educational performance of the faculty members of Tabriz University of Medical Sciences in 2013-14. Methods: Researchers selected 127 faculty members and 1,12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Overall, the empirical result which was obtained in almost the same environment as this current study is the work of Hazratian et al [1]. Hazratian and his co-workers assessed the relationship between educational performance and the three OCB dimensions (conscientious, civic virtue and altruism).…”
Section: Relationship Between Civic Virtue and Employeesmentioning
confidence: 57%
See 2 more Smart Citations
“…Overall, the empirical result which was obtained in almost the same environment as this current study is the work of Hazratian et al [1]. Hazratian and his co-workers assessed the relationship between educational performance and the three OCB dimensions (conscientious, civic virtue and altruism).…”
Section: Relationship Between Civic Virtue and Employeesmentioning
confidence: 57%
“…Baghkhasti and Enayati [11] also obtained similar results with the aforementioned study both in direction and strength. However, Hazratian et al [1] in their study of association between organizational citizenship behavior and educational performance of faculty members in Tabriz University of medical sciences in Iran, they showed that there is no significant relationship between civic virtue and educational performance.…”
Section: Civic Virtuementioning
confidence: 99%
See 1 more Smart Citation